2009
DOI: 10.1029/2008jd011196
|View full text |Cite
|
Sign up to set email alerts
|

Comment on “Plasma chemistry of sprite streamers” by D. D. Sentman, H. C. Stenbaek‐Nielsen, M. G. McHarg, and J. S. Morrill

Abstract: [1] This work raises questions about reaction mechanisms and their ramifications in relation to the model adopted by Sentman et al. (2008). The model adopted by Sentman et al. (2008) for the description of a sprite streamer promoted the {N 2 (a ) + N 2 } quenching reaction rate constant for N 2 (B 3 P g ) formation that is not supported by the conclusions in existing experimental works. It is also shown that there are additional competing chemical reactions forming N 2 (B 3 P g ) which should be taken into acc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…He believed that the reaction of metastable molecules N 2 (A 3 + u ) and O 2 (a 1 g ) might play a more important role in the formation of N 2 (B 3 g ) in the afterglow stage. Moreover, Kamaratos (2009) pointed out that the role of ground state O 2 in producing N 2 (B 3 g ) in a sprite streamer should also be taken into account. Experimental measurements by Umemoto et al (2003) have identified a production of N 2 (B 3 g ) in the collisional deactivation of N 2 (a 1 − u , v=0) by different atomic and molecular gases.…”
Section: Introductionmentioning
confidence: 99%
“…He believed that the reaction of metastable molecules N 2 (A 3 + u ) and O 2 (a 1 g ) might play a more important role in the formation of N 2 (B 3 g ) in the afterglow stage. Moreover, Kamaratos (2009) pointed out that the role of ground state O 2 in producing N 2 (B 3 g ) in a sprite streamer should also be taken into account. Experimental measurements by Umemoto et al (2003) have identified a production of N 2 (B 3 g ) in the collisional deactivation of N 2 (a 1 − u , v=0) by different atomic and molecular gases.…”
Section: Introductionmentioning
confidence: 99%